DEVELOPING CREATIVE THINKING SKILLS IN ECONOMICS SUBJECTS THROUGH A GOOGLE CLASSROOM-BASED BLENDED LEARNING MODEL AND SELF REGULATED LEARNING FOR HIGH SCHOOL STUDENTS - Gandi, Muhammad Rajib; Mardi; Pratama, Aditya (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2023)
This study aims to enhance high school students' creative thinking skills in the field of Economics through the implementation of the Google Classroom-Based Blended Learning model and self-regulated learning strategies. The study's population comprises all students of SMAN 62, with the sample encompassing students from class XI IPS 1 (designated as the control group) and XI IPS 2 (assigned as the experimental group). Employing an experimental approach with a 2x2 factorial design, the research employed questionnaires, pre-tests, and post-tests as data collection tools. The data analysis reveals notable disparities in creative thinking skills between conventional classrooms and blended learning environments. Furthermore, variations in creative thinking skills are observed between students exhibiting low and high levels of self-regulated learning. The study also identifies significant interactions between the learning models and self-regulated learning concerning creative thinking skills. This interaction extends to the distinction in creative thinking skills between conventional classes and blended learning settings for students demonstrating high self-regulated learning as well as those displaying low self-regulated learning. Moreover, the research underscores disparities in creative thinking skills within conventional classes, differentiating students with high and low self-regulated learning. Analogously, differences in creative thinking skills are noted within blended learning classes, differentiating students with high and low self-regulated learning. In conclusion, the study establishes that students' creative thinking skills can be effectively enhanced by deploying the Google Classroom-Based Blended Learning model while cultivating a proactive self-regulated learning disposition. The augmentation of students' creative thinking skills is evident through post-treatment assessments based on a creative thinking indicator questionnaire.